Variation of Small and Large Wild Bee Communities Under Honeybee Pressure in Highly Diverse Natural Habitats - Demeter, Imre; Balog, Adalbert; Sárospataki, Miklós (Frontiers in Ecology and Evolution, 2021)
During the study, the honeybee effects on wild bees were tested and hypothesized that smaller distances from beehives will increase competitions between honeybees and wild bees, while greater distances will have a deleterious effect on competition. The impact on species richness and diversity was tested with distances from beehives, considering that this may differ when large and small wild bee species are considered separately. Altogether 158 species and 13,164 individuals were collected, from which 72% (9,542 individuals) were Apis mellifera. High variation in abundances was detected from one year to another, and the species turnover by sites was 67% in site A, 66% in site V, and 63% in site F. This last one was the site with the previous contact with honeybees. Considering distances from beehives, significant decreases in small bee species diversity were detected from one year to another at each distance except site F, 250 m from hives. The changes in species diversity and community structure of small bee species are detected from one year to another.